Chapter «E la nodosa podagra, con gravissima noia di chi l'ha, tiene tutto il corpo quasi imobile e contratto». Note sul lessico medico-anatomico nel Boccaccio volgare - De Vecchis, Kevin (Studi e saggi, 2022)
After providing a brief description of medicine in the Middle Ages, the work collects and examines the terms attested in three vernacular works by Boccaccio (Decameron, Corbaccio and Esposizioni sopra la Comedia) that can be classified in the medical lexicon. The aim of the paper is to verify the importance that this lexical sector has in Boccaccio's vernacular production, by identifying possible differences (qualitative as well as quantitative) between the three works examined and, through the specific examination of a particular case (the sequence nodosa podagra), to show the usefulness of a more in-depth lexical analysis also to clarify Boccaccio's sources.